Factors Determining Retreatment Time Interval of Rituximab in Korean Patients With Rheumatoid Arthritis - Kim, Ji-Won; Jung, Ju-Yang; Shin, Kichul; Suh, Chang-Hee; Kim, Hyoun-Ah (Frontiers in Medicine, 2021)
Unlike other biologic agents for rheumatoid arthritis (RA) that are administered at regular intervals even without flare, rituximab can be administered according to the timing of retreatment determined by the physician. Recently, there has been a tendency to prefer on-demand administration for disease flares rather than regular retreatment. We aimed to investigate the retreatment patterns of rituximab in patients with RA and to identify factors associated with extension of the time interval between retreatment courses. This study included RA patients on rituximab treatment who were enrolled in the Korean Rheumatology Biologics registry (KOBIO) or treated at Ajou University Hospital. Previous or current concomitant conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs), corticosteroids, number of previous biologic agents, and withdrawal, and time intervals of rituximab retreatment were collected. In case of treatment failure, the reasons such as lack of efficacy, adverse events, and others, were also identified. A total of 82 patients were enrolled. The mean follow-up period from the first cycle of rituximab was 46.1 months, and the mean interval between the retreatment courses was 16.3 months. The persistent rates of rituximab after 5 years was 72.4%. Concomitant use of at least two csDMARDs (β = 4.672; 95% CI: 0.089 ‒ 9.255, p = 0.046) and concomitant use of corticosteroids (β = 7.602; 95% CI: 0.924 ‒ 14.28, p = 0.026) were independent factors for extending the time interval between the retreatment courses. In conclusion, RA patients treated with rituximab in Korea show high persistence rates. Concomitant use of two or more csDMARDs and concomitant use of corticosteroids with rituximab are associating factors of extending the retreatment time interval. These findings should be considered when selecting rituximab as a treatment for patients with RA.